Association of beta-blocker use with less prevalent joint pain and lower opioid requirement in people with osteoarthritis - Valdes, Ana M.; Abhishek, Abhishek; Muir, Kenneth; Zhang, Weiya; Maciewicz, Rose A.; Doherty, Michael (Wiley, 2017)
Objective: Recent findings suggest that β-adrenergic blockers have anti-nociceptive properties. The aim of this study was to compare levels of large joint pain between those on adrenergic blockers and those on other antihypertensive medications. Methods: Data from the GOAL study, a secondary care cohort of osteoarthritis (OA), were used. Joint pain was assessed using the Western Ontario and McMaster Universities Arthritis (WOMAC) pain score in 873 individuals who had symptomatic hip and/or knee OA and hypertension, and who were on ≥1 prescription antihypertensive medications. The association between adrenergic blocker prescription and a) at least moderate joint pain (WOMAC <75), and b) use of prescription analgesics was examined using binary logistic regression. Analyses were adjusted for age, gender, BMI, knee or hip OA, history of joint replacement (at other joints), anxiety and depression. Results: Use of β-adrenergic blockers associated with lower WOMAC pain scores and with a lower prevalence of joint pain after adjustment for demographic variables and comorbidity (adjusted odds ratio (aORpain= 0.68 (95%C.I. 0.51-0.92; p<0.011)). No associations with pain were observed with use of α-blockers (aORpain= 0.94 (95%C.I. 0.55-1.58)) or with any other class of anti-hypertensive medications. Prescription of β-blockers also associated negatively with opioid use (aORopioids=0.73 (95%CI 0.54-0.98; p<0.037)) and with use of prescription analgesics in general (aORanalgesics=0.74 (95%CI 0.56-0.94; p<0.032)). Conclusion: Use of β-blockers associates with less joint pain and lower use of opioids and other analgesics in individuals with symptomatic large joint OA. This observation needs to be confirmed in other studies. This article is protected by copyright. All rights reserved.